Low-dose prostaglandin E1 is safe and effective for critical congenital heart disease: is it time to revisit the dosing guidelines?. (3rd January 2021) - Vari, Daniel; Xiao, Wendi; Behere, Shashank; Spurrier, Ellen; Tsuda, Takeshi; Baffa, Jeanne M.
Abstract: Introduction: Prostaglandin E1 is used to maintain ductal patency in critical congenital heart disease (CHD). The standard starting dose of prostaglandin E1 is 0.05 µg/kg/minute. Lower doses are frequently used, but the efficacy and safety of a low-dose regimen of prostaglandin E1 has not been established. Methods: We investigated neonates with critical CHD who were started on prostaglandin E1 at 0.01 µg/kg/minute. We reviewed 154 consecutive patients who were separated into three anatomical groups: obstruction to systemic circulation, obstruction to pulmonary circulation, and inadequate mixing (d-transposition of the great arteries). Treatment failure rates and two commonly reported side effects, respiratory depression and seizure, were studied. Results: A total of 26 patients (17%) required a dose increase in prostaglandin E1. Patients with pulmonary obstruction were more likely to require higher doses than patients with systemic obstruction (15/49, 31% versus 9/88, 10%, p = 0.003). Twenty-eight per cent of patients developed respiratory depression and 8% of patients needed mechanical ventilation. Prematurity (<37 week gestation) was the primary risk factor for respiratory depression. No patient required dose escalation or tracheal intubation while on transport. No patient had a seizure attributed to prostaglandin E1. Conclusions: Prostaglandin E1 at an initial and maintenance dose of 0.01 µg/kg/minute was sufficient to maintain ductal patency in 83% of our cohort. The incidence of respiratory depression requiring mechanical ventilation was low and was mostly seen in premature infants. Starting low-dose prostaglandin E1 at 0.01 µg/kg/minute is a safe and effective therapy for critical CHD.